Sporotrichosis Cases in Commercial Insurance Data, United States, 2012–2018 - Kaitlin Benedict; Brendan R. Jackson (Emerging Infectious Diseases, 2020)
The geographic distribution of sporotrichosis in the United States is largely unknown. In a large commercial health insurance database, sporotrichosis was rare but most frequently occurred in southern and south-central states. Knowledge about where sporotrichosis is most likely to occur is essential for increasing clinician awareness of this rare fungal disease.